The Monetary Model Strikes Back : Evidence from the World - Cerra, Valerie (IMF Working Papers; Working Paper ;, 2008)
We revisit the dramatic failure of monetary models in explaining exchange rate movements. Using the information content from 98 countries, we find strong evidence for cointegration between nominal exchange rates and monetary fundamentals. We also find fundamentalsbased models very successful in beating a random walk in out-of-sample prediction.